Pengembangan Peran Kepemimpinan Sekolah Untuk Mendorong Integrasi Teknologi Pendidikan - Wahyuli, Alma Aprilia; Riana, Dewi; Lebang, Rita; Haryaka, Usfandi (Sekolah Tinggi Teknologi Industri (STTI) Bontang, 2024)
Education in the digital era requires school principals to play an encouraging and strategic role in utilizing technology to enhance the quality of learning. The purpose of this community service program is to empower school principals in optimizing their role in integrating educational technology. This program employs a qualitative approach with data collection techniques through literature studies, including exploring journals, books, and other relevant information. The results of the service indicate that school principals play a crucial role in improving the quality of education in the digital era. The role of school principals includes the ability to lead and manage the school effectively to utilize digital technology, serve as educators for teachers and staff in developing their technological competencies, and manage school resources, including digital technology, efficiently. Despite facing challenges such as a lack of trained human resources and technological infrastructure constraints, certain strategies can help overcome these obstacles. Training and professional development of teachers are essential steps in enhancing their technology usage skills. Additionally, improving technological infrastructure, such as adequate internet access and sufficient hardware, is necessary to support optimal technology integration.